2017
DOI: 10.5539/ijef.v9n3p168
|View full text |Cite
|
Sign up to set email alerts
|

Educational Gender Gap, Economic Growth and Income Distribution: An Empirical Study of the Interrelationship in Cameroon

Abstract: This study aimed at investigating the interrelationship existing between educational gender gap, economic growth and income distribution in Cameroon using time series data from 1970 to 2014 obtained from the World Bank Development indicators and University of Texas inequality project. For estimation, the three stage least square regression technique was employed to estimate the parameters of the system of equations. The econometrics results showed that, educational gender gap had a positive and significant eff… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
3
0
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(5 citation statements)
references
References 11 publications
1
3
0
1
Order By: Relevance
“…About the external factors, the relationship with the decision to use was 0.610 which implies a medium relationship between the variables, since the dimension includes very strong factors such as cost, security, stability, and availability of technology, the above is in agreement withwhat waspublished by Fonchamnyo (2013) who points out the existence of relationship between these variables.…”
Section: Discussion Of Resultssupporting
confidence: 79%
“…About the external factors, the relationship with the decision to use was 0.610 which implies a medium relationship between the variables, since the dimension includes very strong factors such as cost, security, stability, and availability of technology, the above is in agreement withwhat waspublished by Fonchamnyo (2013) who points out the existence of relationship between these variables.…”
Section: Discussion Of Resultssupporting
confidence: 79%
“…Behavioral adoption (BA) is determined by liking/disliking individuals for an outside reason (Mian & Rizwan, 2013). Behavior Adoption (BA) is the drive of customers to embrace new creative approaches (Fonchamnyo, 2013). Intention to use (INT) depends on the BA (Behavioral Adoption) of the customers towards Islamic mobile banking and BA (Behavioral Adoption) is considered the most important variable of TAM (Technological Acceptance Model) (Sheeran Irani, 2007).…”
Section: Behavioral Adoption (Ba)mentioning
confidence: 99%
“…The result of regression showed that all the determinants of behavior intention explained 56.6%variance where social influence found to be most significant factor in adoption of electronic banking. Fonchamnyo (2013) examined the determinant to customer's perception of internet banking adoption. The study was based on technology acceptance model while incorporating the external factors as well.…”
Section: Objective Of the Studymentioning
confidence: 99%